2013
DOI: 10.9790/2380-0214549
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study On The Endo-Parasitic Infestation In Clarias Gariepinus Collected From Earthen And Concrete Ponds In Makurdi, Benue State, Nigeria

Abstract: The study was conducted to collect and identify endoparasites of Clarias gariepinus from earthenand concrete ponds, Victory Fish Farm, Makurdi, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Relatively higher veracity in males particularly during the competition for food may increase the frequency of contact with the parasites, thereby increasing the chances of infection (Emere, 2000). Current observation is consistent with the reports of Anosike et al (1992) and Omeji (2013) who observed more parasite infestation in male fish than the female. The observation is however at variance with that of (Emere and Egbe, 2006) and Dankishiya et al (2013) who reported higher intensity of helminth parasites in the gastrointestinal tract of female wild African sharp tooth catfish (Clarias gariepinus) in Gwagwalada of Federal Capital Territory, Nigeria than the male counterparts.…”
Section: Discussionsupporting
confidence: 91%
“…Relatively higher veracity in males particularly during the competition for food may increase the frequency of contact with the parasites, thereby increasing the chances of infection (Emere, 2000). Current observation is consistent with the reports of Anosike et al (1992) and Omeji (2013) who observed more parasite infestation in male fish than the female. The observation is however at variance with that of (Emere and Egbe, 2006) and Dankishiya et al (2013) who reported higher intensity of helminth parasites in the gastrointestinal tract of female wild African sharp tooth catfish (Clarias gariepinus) in Gwagwalada of Federal Capital Territory, Nigeria than the male counterparts.…”
Section: Discussionsupporting
confidence: 91%
“…This also, likely suggested the absence of infective organisms in the type of diet of the fish while it is young. In addition, Onwuliri and Mbgemena (1989), Folstad and Karter (1992), Emere (2000) and Omeji et al (2013) observed that heavier fish…”
Section: -Relationship Between Fish Body Weight and Level Of Parasiti...mentioning
confidence: 94%